CONTRIBUTION TO THE STUDY OF GASTROINTESTINAL PARASITISM IN THE GUANACO (LAMA GUANICOE CACSILENSIS) - Castillo D., Hugo (2008)
The aim of this study was to identify the species of gastrointestinal parasites affecting the Peruvian guanaco and to determine the levels of parasitism in the populations under evaluation. For this purpose, 132 fresh faecal samples were collected from nine populations of wild guanacos located in six departments of Peru: Huallhua Community in Ayacucho; Calipuy National Reserve in La Libertad; Chavín community in Ica; Salinas and Aguada Blanca National Reserve, and Machaguay and Yarabamba districts in Arequipa, Quilahuani district and Vila Vilani community in Tacna, and La Capilla district in Moquegua. Samples were processed by the coproparasitological techniques of flotation, sedimentation, larvae culture, and Baerman, and biometry of larvae and oocysts. Eight species of nematodes were identified: Graphinema aucheniae, Bunostomun spp., Ostertagia spp., Trichuris spp., Cooperia spp., Nematodirus spp., Mazamastrongylus peruvianus and Trichostrongylus spp., and four Eimeria species: E. lamae, E. alpacae, E. punoensis and E. macusaniensis. All guanaco populations had at least one animal with parasites, showing low parasite burden in general, and with a variation in the frequency of gastrointestinal parasitism from one population to another, depending on the habitat and the proximity to other domestic herbivores.